Glucose and Nitrogen Regulate the Switch from Histone Deacetylation to Acetylation for Expression of Early Meiosis-Specific Genes in Budding Yeast - Pnueli, Lilach (American Society for Microbiology, 2004)
In eukaryotes, the switch between alternative developmental pathways is mainly attributed to a switch in transcriptional programs. A major mode in this switch is the transition between histone deacetylation and acetylation. In budding yeast, early meiosis-specific genes (EMGs) are repressed in the mitotic cell cycle by active deacetylation of their histones. Transcriptional activation of these genes in response to the meiotic signals (i.e., glucose and nitrogen depletion) requires histone acetylation. Here we follow how this regulated switch is accomplished, demonstrating the existence of two parallel mechanisms. (i) We demonstrate that depletion of glucose and nitrogen leads to a transient replacement of the histone deacetylase (HDAC) complex on the promoters of EMG by the transcriptional activator Ime1. The occupancy by either component occurs independently of the presence or absence of the other. Removal of the HDAC complex depends on the protein kinase Rim15, whose activity in the presence of nutrients is inhibited by protein kinase A phosphorylation. (ii) In the absence of glucose, HDAC loses its ability to repress transcription, even if this repression complex is directly bound to a promoter. We show that this relief of repression depends on Ime1, as well as on the kinase activity of Rim11, a glycogen synthase kinase 3β homolog that phosphorylates Ime1. We further show that the glucose signal is transmitted through Rim11. In cells expressing the constitutive active rim11-3SA allele, HDAC repression in glucose medium is impaired.